Climate Change and Poverty : An Analytical Framework - Hallegatte, Stephane; Bangalore, Mook; Bonzanigo, Laura; Fay, Marianne; Narloch, Ulf; Rozenberg, Julie; Vogt-Schilb, Adrien (World Bank Group, Washington, DC, 2014)
Climate change and climate policies will affect poverty reduction efforts through direct and immediate impacts on the poor and by affecting factors that condition poverty reduction, such as economic growth. This paper explores this relation between climate change and policies and poverty outcomes by examining three questions: the (static) impact on poor people's livelihood and well-being; the impact on the risk for non-poor individuals to fall into poverty; and the impact on the ability of poor people to escape poverty. The paper proposes four channels that determine household consumption and through which households may escape or fall into poverty (prices, assets, productivity, and opportunities). It then discusses whether and how these channels are affected by climate change and climate policies, focusing on the exposure, vulnerability, and ability to adapt of the poor (and those vulnerable to poverty). It reviews the existing literature and offers three major conclusions. First, climate change is likely to represent a major obstacle to a sustained eradication of poverty. Second, climate policies are compatible with poverty reduction provided that (i) poverty concerns are carefully taken into account in their design and (ii) they are accompanied by the appropriate set of social policies. Third, climate change does not modify how poverty policies should be designed, but it creates greater needs and more urgency. The scale issue is explained by the fact that climate will cause more frequent and more severe shocks; the urgency, by the need to exploit the window of opportunity given to us before climate impacts are likely to substantially increase.